Converting CO2 into heterocyclic compounds under accelerated performance through Fe3O4-grafted ionic liquid catalysts. (24th January 2022) - Vishwakarma, Niraj K.; Singh, Shikha; Vishwakarma, Sambhav; Sahi, Ajay Kumar; Patel, Vijay Kumar; Kant, Shiva; Mahto, Sanjeev Kumar
Abstract : Solid supported catalysts such as amines are in high demand for the chemical fixation of CO2 into commodity chemicals. Abstract : Solid supported catalysts such as amines are in high demand for the chemical fixation of CO2 into commodity chemicals. Here, we demonstrate an accelerated platform for 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU)-ionic liquid (IL) catalyzed CO2 fixation via the grafting of DBU-ILs over magnetically separable Fe3 O4 nanoparticles (MNPs). The DBU-ILs were covalently immobilized over Fe3 O4 MNPs utilizing the thio–ene reaction of allyl-DBU with –SH modified Fe3 O4 MNPs. The DBU-IL-grafted Fe3 O4 (Fe3 O4 @DBU-ILs) materials were characterized by Fourier-transform infrared (FT-IR) spectroscopy, field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA) and vibrating-sample magnetometry (VSM). TEM revealed that the MNPs have a spherical structure with a particle size of 12–20 nm. VSM showed the gradual decrease in magnetization after stepwise grafting from Fe3 O4 to Fe3 O4 @DBU-ILs. The efficacy of the two different Fe3 O4 @DBU-ILs, Fe3 O4 @[HDBU + ][TFE − ] and Fe3 O4 @[HDBU + ][AcO − ] prepared by neutralization of  Fe3 O4 @DBU with 2, 2, 2-trifluoroethanol (TFE) and acetic acid (AcOH), was investigated by simultaneous fixation of CO2 into the important heterocyclic compounds quinazoline-2, 4(1 H, 3 H )-dione and benzimidazolone. This approach shows excellent recyclability with a nominal decrease (2–3%) in product yields after each cycle. In particular, the energy-dispersive X-ray spectroscopy (EDX) mapping of Fe3 O4 @[HDBU + ][TFE − ] used for five cycles demonstrated significant leaching of TFE. Interestingly, after retreatment with TFE, Fe3 O4 @[HDBU + ][TFE − ] showed a similar yield to that of a fresh catalyst.